Papers - Lead - A Brief History of Blast-furnace Lead Smelting in America - Arthur S. Dwight (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1937)
We author of this historical chapter will perhaps be criticized for limiting his subject to the history of the blast furnace in lead smelting, and especially to the part it played in the great custom ore-smelting business which for three decades or more was the means of opening up vast mineral treasures and practically dominated the mining industry in the Rocky Mountain region of the United States, in Mexico and in Canada. The men of that era shared the romance and the thrills of mining, and bore their part as pioneers in the building of the great West. The present writer was too young to participate in the first of the three decades mentioned, but immediately thereafter came under the apprenticeship of some of the men who had worked out the early metallurgical problems of the industry, became personally acquainted with most of the others of that group, heard the tales of early experiences, successes and failures, the gossip of the frontier and mining camps, from all of which there remain embedded in his mind clear impressions of the outstanding personalities of that time. That is the background against which the fifty years of intimate contact with the mining and smelting business and his own experiences as metallurgist stand out in his memory, and it is hoped that the gentle reader may understand and approve his desire to rescue from comparative oblivion the fundamentally valuable results accomplished by these fathers of the industry. It will be the purpose of this chapter first to narrate the general history of the growth of the industry; second, to pay tribute to some of the pioneer metallurgists, and third, to discuss some of the salient points of the metallurgical practice at different periods, to illustrate the technical progress of the art. The series of eight Annual Reports of Rossiter W. Raymondl,† U. S. Commissioner of Mining Statistics from 1869 to 1876, contain most of the available information about the early smelting operations in the Rocky Mountain region, and much is in the early volumes of the Transactions of the American Institute of Mining Engineers. The monograph by S. F. Emmons2 though not published until 1886, contained an elaborate description of the smelting works operating in 1879. Otto H. Hahn3 wrote a valuable paper in 1883, on smelting prac-